Improvement in strength of SiC reticulated porous ceramics. (2nd January 2016) - Zhao, J.; Ru, H.; Xu, Y.; Chang, L.; Wang, W.; Yue, X.; Zhang, C.
Abstract : Silicon carbide reticulated porous ceramics (SiC RPCs) were fabricated via polymer sponge technique. In order to obtain SiC RPCs with optimised mechanical performance, influence of sintering holding time, silica fume content and particle size distribution has been investigated in details. It was found that sintering holding time and content of silica fume have influence on the physical and mechanical properties of SiC RPCs, and the optimal value were 2 h and 17 mass-% respectively. At the same time, to thicken the struts, the recoating technique has been applied, through which mechanical strength has been improved significantly.